Enhanced thermoelectric performance in Mg3+xSb1.5Bi0.49Te0.01via engineering microstructure through melt-centrifugation. Issue 3 (4th January 2021) - Ozen, Melis; Yahyaoglu, Mujde; Candolfi, Christophe; Veremchuk, Igor; Kaiser, Felix; Burkhardt, Ulrich; Snyder, G. Jeffrey; Grin, Yuri; Aydemir, Umut
Abstract : By applying the melt-centrifugation, porosity and dislocations are introduced in the microstructure of the n-type Zintl phase Mg3+ x Sb1.5 Bi0.49 Te0.01 leading to significantly low κ l (∼ 0.33 W m −1 K −1 at 723 K) and enhanced zT (∼ 1.64 at 723 K). Abstract : N-type Zintl phases with earth-abundant and non-toxic constituent elements have attracted intense research interest thanks to their high thermoelectric efficiencies in the mid-temperature range, exemplified by the recently discovered Mg3 Sb2 material. In this study, the liquid phase is expelled from the microstructure of the optimized n-type phase Mg3+ x Sb1.5 Bi0.49 Te0.01 by applying a melt-centrifugation technique leading to the formation of lattice dislocations, grain boundary dislocations and increasing porosity. Additional phonon scattering mechanisms were introduced in the microstructure through this manufacturing method, resulting in a significant 50% reduction in the total thermal conductivity from ∼1 W m −1 K −1 to ∼0.5 W m −1 K −1 at 723 K. Combined with high power factors, this reduced heat transport leads to a dimensionless thermoelectric figure of merit, zT, value of ∼1.64 at 723 K, 43% higher than the value obtained in untreated Mg3+ x Sb1.5 Bi0.49 Te0.01 ( zT ∼ 1.14 at 723 K). This peak zT value yields a predicted device ZT of 0.95, and a promising theoretical thermoelectric efficiency of about 12%. These results further underline the great potential of the lightweight Mg3 Sb2 material for mid-temperature energy harvesting via thermoelectric effects.